In vitro Antimicrobial Activity of Royleanone Derivatives Against Gram‐Positive Bacterial Pathogens. (11th March 2013) - Rijo, Patrícia; Duarte, Aida; Francisco, Ana Paula; Semedo‐Lemsaddek, Teresa; Simões, Maria Fátima
<x xml:space="preserve">Abstract</x> Infections caused by multiresistant bacterial pathogens are a significant problem worldwide, turning the search for natural compounds to act as alternatives to antibiotics of major importance. The aim of the present study was to investigate the in vitro antimicrobial activity of 7α‐acetoxy‐6β‐hydroxyroyleanone (1), isolated from Plectranthus grandidentatus (Lamiaceae), and 11 additional royleanone abietane derivatives of 1 (2–12) against important Gram‐positive human bacterial pathogens. Results showed that the aromatic and alkylic esters 2, 3 and 5 are more active than 1 against Enterococcus and Staphylococcus (minimum inhibitory concentration (MIC) values ranging from 0.98 to 62.50 µg/mL). Moreover, 7α‐acetoxy‐6β‐hydroxy‐12‐O‐(4‐chloro)benzoylroyleanone (2) gave rise to a new antibacterial‐prototype (MIC values of 3.91–15.63 µg/mL against Staphylococcus and of 0.98–3.91 µg/mL against Enterococcus). The results showed that the compounds under analysis also present antimicrobial activity against resistant bacteria. The hydrophobic extra‐interactions with bacterial targets seem to play an important role on the activity of royleanones derivatives. Copyright © 2013 John Wiley & Sons, Ltd.